Preparation method of electron-rich metal organic framework SO2 adsorbent

By designing a two-dimensional MOF material formed by coordination between tridentate carboxylic acid-based ligands with metal zirconium ions with electron-rich nitrogen-containing groups, the problems of SO2 adsorption and desorption stability and selectivity in the prior art are solved, and an efficient and economical SO2 capture effect is achieved.

CN119613751AActive Publication Date: 2025-03-14STATE GRID FUJIAN ELECTRIC POWER RES INST +2
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411805482.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-10
Publication Date
2025-03-14
Estimated Expiration
2044-12-10

AI Technical Summary

Technical Problem

The prior art has stability problems and complex synthesis processes in the adsorption and desorption of SO2 gases, and the selective adsorption characteristics of SO2 are insufficient, especially difficult to desorption at high temperatures.

Method used

By designing a two-dimensional MOF material formed by coordination between tridentate carboxylic acid-based ligands containing electron-rich and nitrogen-rich groups and metal zirconium ions, the strong interaction between electron-rich groups and SO2 is used to improve adsorption performance and simplify the preparation process.

Benefits of technology

It achieves efficient adsorption and easy desorption, significantly improving the selectivity and adsorption efficiency of SO2, and the material has good chemical stability and resistance to strong acids and alkalis.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119613751A_ABST
    Figure CN119613751A_ABST
Patent Text Reader

Abstract

The invention relates to a preparation method of an electron-rich metal organic framework SO2 adsorbent. According to the material, tridentate carboxylic acid H3BTB-NH2 or H3TPY containing electron-rich nitrogen groups is introduced to be effectively coordinated with metal clusters to form the two-dimensional MOF material. The electron-rich groups have relatively strong electron-donating ability, and can generate electron-donating interaction with SO2 molecules, so that the adsorption ability of SO2 is enhanced, and relatively easy desorption conditions are ensured. Different positions of nitrogen-containing groups in a metal organic framework structure have obvious influence on the SO2 adsorption performance of the material, different types of nitrogen-containing groups are introduced into a tridentate carboxylic acid organic ligand of the MOF material designed by the invention, so that the spatial sites and electronic characteristics of the nitrogen groups are adjusted, the SO2 adsorption capacity is further optimized, and the SO2 adsorption performance is improved. And not only is efficient adsorption and desorption of SO2 realized, but also a foundation is laid for subsequent research and development of environmental governance materials.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the fields of materials science and environmental engineering, in particular, the design, preparation and application of metal organic framework (MOF) materials. Specifically, the present invention focuses on the application of two-dimensional, stable MOF materials formed by coordination of tridentate carboxylic acid-based ligands containing electron-rich nitrogen-containing groups and metal clusters in SO2 gas adsorption. By optimizing the position and electronic properties of the nitrogen-containing groups in the tridentate carboxylic acid organic ligands, the formed two-dimensional zirconium-based MOF materials are endowed with certain electron-rich properties. By means of the suitable interaction between the electron-rich groups and SO2 gas, the adsorption performance of the prepared MOF material for SO2 is improved and easier desorption conditions are guaranteed, and the simple "one-pot" preparation of the relevant electron-rich MOF materials is realized, thereby providing a new type of efficient material solution for environmental governance and gas adsorption technology. This technology has important application prospects in the fields of industrial waste gas treatment, environmental pollution control and sustainable development. Background Art

[0002] Sulfur dioxide (SO2) is a corrosive and irritating gas that is widely present in industrial production and fuel combustion processes. Its emissions not only have a serious impact on air quality, but also pose a threat to human health. Long-term exposure to SO2 environment may cause health problems such as respiratory diseases and skin allergies. At the same time, acid rain formed by the reaction of SO2 and water will lead to soil acidification, water pollution and destruction of the ecosystem, thus causing a series of environmental problems. Therefore, it is particularly important to effectively remove SO2 gas, especially in the application of industrial waste gas treatment.

[0003] At present, gas adsorption technology is one of the main means of removing SO2. Among the many adsorption materials, metal organic framework (MOF) materials have attracted much attention due to their unique structure and excellent performance. MOF materials are self-assembled by metal ions and organic ligands, and have high specific surface area, adjustable pore structure, host-guest interaction, and good chemical and thermal stability. This makes MOF show great application potential in gas separation and adsorption. Studies have shown that compared with traditional adsorbent materials such as metal oxides (such as MnOx, CuO, ZnO, etc.), activated carbon, zeolite, etc., MOF materials with specific topological structures, functional groups, and pore sizes show better capture ability for SO2, and can efficiently remove SO2 at lower concentrations, providing a good foundation for its application in environmental governance. By using the bidentate carboxylic acid ligand functionalized with urea groups to coordinate with divalent zinc ions, and using 4,4′-bipyridine to coordinate with the divalent zinc ions with the axial paddle wheel structure formed above, a three-dimensional extended MOF network structure can be formed, which can significantly improve the capture capacity of SO2 and NH3 (ACS Appl. Mater. Interfaces 2017, 9, 37419−37434); the higher adsorption amount is attributed to the strong hydrogen bond interaction between urea groups and SO2 and NH3. However, the stability of the formed MOF is problematic (ACS Appl. Mater. Interfaces 2017, 9, 37419−37434), and the synthesis process is relatively complicated. In addition, although inorganic high nitrogen carbonyl zirconium phosphate broad-spectrum adsorbent (CN113101891 A) can be obtained by using melamine zirconium complex and chitosan formaldehyde polymer, dipping in metal salt solution and then sintering at high temperature, it lacks selective adsorption characteristics for SO2 and requires high temperature for desorption. Therefore, it is very important to design and prepare adsorbent materials with high adsorption capacity and easy desorption for SO2 through reasonable structure (topological structure, functional group, etc.) for efficient capture and treatment of SO2.

[0004] The present invention has found that the introduction of nitrogen-containing electron-rich groups into the framework structure constructed by tridentate carboxylic acid ligands and metal zirconium ions can enhance the adsorption performance of zirconium-based MOF materials. The electron-rich group can not only effectively interact with SO2 molecules through electron donation, but also improve the selectivity of the material. For example, nitrogen-containing groups, due to their excellent electron-donating properties, can form strong interactions with sulfur atoms in SO2, thereby improving the adsorption capacity. At the same time, unlike zeolite or molecular sieve adsorbent materials, the relatively moderate host-guest interaction between SO2 and the framework material can ensure that it is relatively easy to desorb SO2, thereby avoiding high-temperature heating. At the same time, the designed and synthesized two-dimensional electron-rich zirconium-based MOF material can be simply and batch-prepared through a "one-pot method", laying the foundation for subsequent batch preparation and application in related fields. The present invention is dedicated to developing a two-dimensional, highly stable zirconium-based MOF material containing electron-rich groups. Two types of tridentate carboxylic acid ligands (H3BTB-NH2 and H3TPY) containing electron-rich nitrogen groups are used to effectively coordinate with metal clusters to obtain a two-dimensional MOF material with excellent solubility and processability and resistance to strong acids and bases, so as to improve its adsorption performance for SO2. By regulating the position of the nitrogen group, its performance in the SO2 adsorption process is studied, aiming to achieve efficient adsorption and easier desorption of SO2. This study not only provides a new idea for the efficient capture of SO2, but also lays the foundation for the further development and application of metal organic framework materials. By optimizing the structure and performance of MOF, the present invention hopes to provide a more efficient, economical and sustainable solution for industrial gas treatment and environmental protection. Summary of the invention

[0005] The purpose of the present invention is to provide a method for preparing a type of electron-rich metal organic framework SO2 adsorbent, using a simple solvent thermal synthesis strategy and promoting the rapid formation of materials by rationally designing the ratio of reactants and reaction time; the two-dimensional nanosheets generated by this method not only have a large specific surface area, but also have good structural stability, which helps to improve the adsorption capacity of SO2.

[0006] To achieve the above purpose, the technical solution adopted by the present invention is: design and synthesize electron-rich nitrogen group metal organic framework to enhance SO2 adsorption performance, and through a simple hot solvent synthesis strategy, the rapid formation of nanosheets can be effectively promoted. The two-dimensional nanosheets generated by this method not only have a large specific surface area, but also show good structural stability, thereby significantly improving the adsorption capacity of SO2. At the same time, the selected organic ligand contains electron-rich groups, and the strong interaction between the electron-rich groups and SO2 is used to give the prepared material excellent SO2 adsorption capacity.

[0007] To achieve the above object, according to another aspect of the present invention, a scheme for designing and synthesizing electron-rich nitrogen group organic ligands coordinated with zirconium ions to form a metal organic framework to enhance SO2 adsorption performance is provided, comprising the following steps: S1. Add ZrCl4 (0.128-0.132 mmol) and H3BTB-NH2 (30.9-40.2 mg) to DMF to obtain a mixed solution, add ultrapure water (4.0-4.2 ml) and formic acid (4.0-4.2 ml) to the mixed solution, and subject the mixed solution to ultrasonic treatment (15-20 minutes). After the ultrasonic treatment, heat the mixed solution in a reactor (120 °C). After reacting for 24 hours, the obtained light brown suspension is centrifuged and washed several times to finally obtain a uniformly dispersed, strong acid and alkali resistant Zr-BTB-NH2 nanosheet suspension.

[0008] S2. ZrCl4 (0.128-0.132 mmol) and H3TPY (28.2-28.4 mg) were added to DMF to obtain a mixed solution. Ultrapure water (4.0-4.2 ml) and formic acid (4.0-4.2 ml) were added to the mixed solution. The mixed solution was subjected to ultrasonic treatment (15-20 minutes). After the ultrasonic treatment, the mixed solution was heated in a reactor (120 °C). After reacting for 24 hours, the obtained lavender suspension was centrifuged and washed several times to finally obtain a uniformly dispersed, strong acid and alkali resistant Zr-TPY nanosheet suspension.

[0009] As a further optimization of the preparation method of a type of electron-rich metal organic framework SO2 adsorbent of the present invention: the H3BTB-NH2: 1,1':3',1''-Terphenyl]-4,4''-dicarboxylicacid, 3,3''-diamino-5'-(3-amino-4-carboxyphenyl, CAS: 1660960-30-4. The H3TPY: 4'-(4-carboxyphenyl)-[2,2':6',2''-terpyridine]-5,5''-dicarboxylic acid, CAS No.: 1887067-79-9.

[0010] The structure of the H3BTB-NH2 is as follows: ; The structure of H3TPY is as follows: .

[0011] As a further optimization of the preparation method of a type of electron-rich metal organic framework SO2 adsorbent of the present invention: the molar ratio of the added amounts of ZrCl4 and H3BTB-NH2 in step S1 is 1.9:1-2.0:1, and the molar ratio of the added amounts of ZrCl4 and H3TPY in S2 is 1.9:1-2.0:1.

[0012] As a further optimization of the preparation method of a class of electron-rich metal organic framework SO2 adsorbents of the present invention: the added amount of the DMF solvent is 30.0-30.2 ml.

[0013] As a further optimization of the preparation method of a class of electron-rich metal organic framework SO2 adsorbents of the present invention: the amount of ultrapure water added is 4.0-4.2 ml.

[0014] As a further optimization of the preparation method of a class of electron-rich metal organic framework SO2 adsorbents of the present invention: the amount of formic acid added is 4.0-4.2 ml.

[0015] As a further optimization of the preparation method of a type of electron-rich metal organic framework SO2 adsorbent of the present invention: the power of the ultrasound is 200-300 W, and the cumulative ultrasound time is 15-20 min.

[0016] As a further optimization of the preparation method of a class of electron-rich metal organic framework SO2 adsorbents of the present invention: the oven heating temperature is 120°C and the heating time is 24 h.

[0017] As a further optimization of the preparation method of a class of electron-rich metal organic framework SO2 adsorbents of the present invention: the centrifugal speed in step S2 is 8000-10000 r·min -1 , centrifugation time 5-6 min, and centrifugation washing operation at least 5 times.

[0018] Application: The Zr-BTB-NH2 or Zr-TPY nanosheet suspension is dried and used as a SO2 adsorbent for SO2 gas adsorption. The mass of the dried Zr-BTB-NH2 and Zr-TPY powder used for testing is not less than 100 mg.

[0019] In general, the above technical solution conceived by the present invention has the following beneficial effects compared with the prior art: 1. The present invention adopts a hot solvent method to synthesize two-dimensional MOF nanosheets. The process is simple and easy to control, and the required operating conditions are mild, which makes the preparation of the material more efficient and rapid, and can be applied on a large scale in industrial production, reducing production costs.

[0020] 2. The synthesized two-dimensional Zr-BTB-NH2 and Zr-TPY nanosheets have a high specific surface area, providing more active sites, greatly enhancing their gas adsorption capacity, especially in the adsorption of SO2, which can effectively remove harmful gases in the air and improve environmental quality. At the same time, the two-dimensional MOF nanosheets synthesized by the "one-pot method" can withstand the etching of strong acids and strong bases, and their topological structure is basically unchanged after treatment with strong acids or strong bases.

[0021] 3. The design of electron-rich groups enables a strong interaction between organic ligands and SO2, significantly improving the selectivity and adsorption efficiency of the material for SO2. The maximum SO2 adsorption capacity of Zr-TPY at 1 bar pressure is 66.3 cm 3 ·g -1 , and more than 95% desorption can be achieved at room temperature. BRIEF DESCRIPTION OF THE DRAWINGS

[0022] Figure 1 The XRD (ab) and infrared spectra (cd) of Zr-BTB-NH2 and Zr-TPY nanosheets prepared in Example 1 and Example 2; Figure 2 is the XRD spectrum of the Zr-BTB-NH2 nanosheets prepared in Example 1 before and after being treated with strong acid and strong base for 12 hours; Figure 3 is a scanning electron microscope image of Zr-BTB-NH2 and Zr-TPY nanosheets prepared in Example 1 and Example 2; Figure 4 is the N2 isotherm adsorption curve of Zr-BTB-NH2 and Zr-TPY nanosheets prepared in Example 1 and Example 2; Figure 5 The adsorption of SO2 by Zr-BTB-NH2 and Zr-TPY nanosheets prepared in Example 1 and Example 2 under different pressures. DETAILED DESCRIPTION

[0023] In order to make the purpose, technical solutions and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the accompanying drawings and embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not intended to limit the present invention. In addition, the technical features involved in each embodiment of the present invention described below can be combined with each other as long as they do not conflict with each other. The present invention is further described in detail below in conjunction with specific embodiments.

[0024] <Example 1> The following is an example of Zr-BTB-NH2 with SO2 adsorption performance, and its preparation method includes the following steps: (1) Preparation of mixed solution: 0.128 mmol ZrCl4 and 30.9 mg H3BTB-NH2 were added to 30 ml DMF, and 4.0 ml ultrapure water and 4.0 ml formic acid were added to the mixed solution to obtain a mixed solution.

[0025] (2) Preparation of Zr-BTB-NH2 nanosheets The mixed solution obtained in step (1) was subjected to water bath ultrasound for 15 minutes. After the ultrasound was completed, the mixed solution was placed in a reactor for heating reaction, wherein the oven heating temperature was 120°C and the heating time was 24 hours. After the reaction was completed, the obtained light brown suspension was centrifuged and washed, wherein the centrifugal speed was 8000 r·min -1 The centrifugation time is about 5 minutes, and the centrifugal washing operation is performed 5 times. Then the washed light brown suspension is dried under vacuum at 150 °C to obtain Zr-BTB-NH2.

[0026] (3) Zr-BTB-NH2 material pretreatment The Zr-BTB-NH2 powder was placed in a vacuum drying oven at 100 °C for 12 h to remove moisture and volatile substances. The dried sample was cooled to room temperature under an inert gas atmosphere.

[0027] (4) SO2 adsorption test Use inert gas (N2) to purge the test system for 15-30 minutes to ensure that there is no impurity gas in the equipment. Place the pretreated Zr-BTB-NH2 powder evenly in the sample chamber of the adsorption test equipment to ensure that it is well dispersed. Slowly introduce a known concentration of SO2 gas (1000 ppm) into the test equipment, ensure that the gas flow is stable, set the test temperature (28 °C), keep the temperature constant, and record the temperature data.

[0028] Example 1 shows the preparation method of SO2 adsorption material based on Zr-BTB-NH2. However, the above scheme is not limited to the development of SO2 adsorption material. In fact, this gas adsorption material can also be extended to other types of target gases.

[0029] <Example 2> Based on the aforementioned Zr-BTB-NH2 as the SO2 adsorption material, the present invention further synthesizes Zr-TPY nanosheets, and the preparation method thereof comprises the following steps: (1) Preparation of mixed solution: 0.128 mmol ZrCl4 and 28.2 mg H3TPY were added to 30 ml DMF, and 4.0 ml ultrapure water and 4.0 ml formic acid were added to the mixed solution to obtain a mixed solution.

[0030] (2) Preparation of Zr-TPY Nanosheets The mixed solution obtained in step (1) was subjected to water bath sonication for 15 minutes. After the sonication, the mixed solution was placed in a reaction kettle for heating reaction. Among them, the heating temperature in the oven was 120 °C and the heating time was 24 h. After the reaction, the obtained light brown suspension was centrifuged and washed. Among them, the centrifugation speed was 8000 r / min, the centrifugation time was about 5 min, and the centrifugation and washing operation was performed 5 times. Subsequently, the washed light brown suspension was dried under vacuum at 150 °C to obtain Zr-TPY.

[0031] (3) Pretreatment of Zr-TPY Material The Zr-TPY powder was placed in a vacuum drying oven, the temperature was set at 100 °C, and it was dried for 12 hours to remove moisture and volatile substances. The dried sample was cooled to room temperature under an inert gas atmosphere.

[0032] (4) SO2 Adsorption Test The test system was purged with an inert gas (N2) for 15 - 30 minutes to ensure that there were no impurity gases in the equipment. The pretreated Zr-TPY powder was evenly placed in the sample chamber of the adsorption test equipment to ensure good dispersion. A known concentration of SO2 gas (1000 ppm) was slowly introduced into the test equipment to ensure stable gas flow. The test temperature (28 °C) was set and the temperature was kept constant, and the temperature data was recorded.

[0033] Example 2 demonstrates a preparation method of a SO2 adsorption material based on Zr-TPY. However, the above scheme is not limited to the development of SO2 adsorption materials. In fact, this gas adsorption material can also be extended to other types of target gases.

[0034] <Morphology and Structure Characterization of Zr-BTB-NH2 and Zr-TPY> A. Structure Characterization 6 mg of each of the Zr-BTB-NH2 and Zr-TPY nanomaterials prepared in Example 1 and Example 2 were taken for XRD testing. Then, 1 mg of each of the Zr-BTB-NH2 and Zr-TPY nanomaterials prepared in Example 1 and Example 2 was taken for infrared spectroscopy testing.

[0035] As Figure 1As shown in (a-b), Zr-BTB-NH2 and Zr-TPY nanosheets exhibit similar characteristic peaks in the XRD pattern, indicating that these two materials have high crystallinity. Meanwhile, the appearance of diffraction peaks such as

[100] /

[010] shows good long-range order in the ab plane. The weaker peaks appearing in the

[001] direction indicate relatively poor long-range order along the c direction, which is consistent with the structural expectation of two-dimensional materials and reflects obvious orientation along the c-axis direction. As Figure 1 shown in (c-d), it can be seen from the infrared spectrum that the stretching vibration peak near 1680 cm -1 is attributed to the stretching vibration of the -C-N bond on H3TPY. As Figure 1 shown in (c-d), it can be seen from the infrared spectrum that the stretching vibration peak near 1505 cm -1 is attributed to the stretching vibration of -N-H on H3BTB-NH2, and the stretching vibration peak near 1654 cm -1 is attributed to the stretching vibration of the -C-N bond on H3TPY, indicating the stable existence of electron-rich nitrogen-containing groups in the MOF. In addition, the prepared MOF materials exhibit excellent chemical stability and can withstand strong acid and strong base environments (as Figure 2 shown).

[0036] B. Morphology Characterization Take 1 mL of the dispersion liquids of the Zr-BTB-NH2 and Zr-TPY nanomaterials prepared in Example 1 and Example 2 respectively and add them to centrifuge tubes, add 5 mL of ethanol for dilution, take 6 microliters each and drop them onto silicon wafers, and observe under a scanning electron microscope.

[0037] As Figure 3 shown, it can be seen from the scanning electron microscope (SEM) photos that the Zr-BTB-NH2 nanosheets stack to form a uniform and dense film, and the surface shows good flatness and uniformity. In contrast, the morphology of Zr-TPY is relatively uneven, with obvious wrinkled structures.

[0038] <Specific Surface Areas of Zr-BTB-NH2 and Zr-TPY> Take 80 mg each of the Zr-BTB-NH2 and Zr-TPY nanomaterials prepared in Example 1 and Example 2 for N2 isothermal adsorption and desorption tests.

[0039] As Figure 4 shown, the specific surface areas of Zr-BTB-NH2 and Zr-TPY are 256.5 m 2 ·g -1 、483.7 m 2 ·g -1, the pore size distribution is mainly concentrated at 6.7 Å. The larger specific surface area provides more active sites for the nanosheets, thus enhancing their SO2 adsorption capacity. This property gives Zr-BTB-NH2 and Zr-TPY potential advantages in gas adsorption applications and enables more effective removal of SO2 from the environment.

[0040] <SO2 Adsorption Performance of Zr-BTB-NH2 and Zr-TPY> Take 100 mg each of the Zr-BTB-NH2 and Zr-TPY nanomaterials prepared in Example 1 and Example 2 for SO2 adsorption testing.

[0041] The specific gas adsorption process is as follows. First, place the Zr-BTB-NH2 and Zr-TPY powders in a vacuum drying oven, set the temperature to 100 °C, and dry for 12 hours to remove moisture and volatile substances. Then, cool the dried samples to room temperature under an inert gas atmosphere. Purge the adsorption test system with an inert gas (N2) for 15 - 30 minutes to ensure there are no impurity gases in the equipment. Place the pretreated Zr-BTB-NH2 and Zr-TPY powders evenly in the sample chamber of the adsorption test equipment to ensure good dispersion.

[0042] After the samples are placed, slowly introduce 1000 ppm of SO2 gas, set the flow rate to the required value (such as 50 mL·min -1 ), and continuously introduce it for 4 - 6 hours to ensure that the samples are fully exposed to the SO2 gas. Use a gas analyzer to monitor the change in SO2 concentration in the sample chamber in real time, record the initial concentration and the concentration data at different time points during the adsorption process, record every 10 minutes until adsorption equilibrium.

[0043] As Figure 5 shown, at 300 K and 1 bar, the maximum SO2 adsorption capacities of Zr-BTB-NH2 and Zr-TPY are 39.3 cm 3 ·g -1 (1.75 mmol g -1 ) and 66.3 cm 3 ·g -1 (2.96 mmol g -1 ), respectively. The adsorption capacity of Zr-TPY is higher than the maximum adsorption capacity of 2.29 mmol⋅g -1 of CPL-1-NH2 constructed with aminopyrazine-2,3-dicarboxylic acid reported at 298 K and 1 bar (Separation and Purification Technology, 2022, 295, 121337.), NPC-3 (maximum adsorption capacity 2.15 mmol⋅g-1 ), NPC-2 (maximum adsorption capacity 1.44 mmol⋅g -1 ) and NPC-1 (maximum adsorption capacity 1.08mmol⋅g -1 ) (Chemical Engineering Journal 2016, 290, 116-124.) and other materials. At the same time, compared with the nitrogen-free Zr-BTBMOF material (the SO2 saturation adsorption capacity at 300 K and 1 bar is 22.5 cm 3 ·g -1 ), and its adsorption capacity for SO2 is significantly improved. The hysteresis loop between the adsorption and desorption isotherms can be attributed to the strong interaction between SO2 and the nitrogen-containing framework material, which also verifies the design concept of achieving efficient capture of SO2 by introducing nitrogen-containing groups into the framework material.

[0044] It is to be understood that the embodiments of the system described above are merely illustrative, and the units described as separate components may or may not be physically separated, and may be located in one place, or may be distributed on different network units. Some or all of the modules may be selected according to actual needs to achieve the purpose of the solution of this embodiment. Those of ordinary skill in the art may understand and implement the solution without creative effort.

[0045] In addition, it should be understood by those skilled in the art that, in the application documents of the embodiments of the present invention, the terms "include", "comprise" or any other variants thereof are intended to cover non-exclusive inclusion, so that a process, method, article or device including a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process, method, article or device. In the absence of further restrictions, an element defined by the sentence "comprises a ..." does not exclude the presence of other identical elements in the process, method, article or device including the element.

[0046] In the description of the embodiment of the present invention, a lot of specific details are described. However, it should be understood that the embodiment of the embodiment of the present invention can be practiced without these specific details. In some examples, well-known methods, structures and techniques are not shown in detail so as not to obscure the understanding of this specification. Similarly, it should be understood that in order to simplify the disclosure of the embodiment of the present invention and help understand one or more of the various inventive aspects, in the above description of the exemplary embodiment of the embodiment of the present invention, the various features of the embodiment of the present invention are sometimes grouped together into a single embodiment, figure, or description thereof. However, the disclosed method should not be interpreted as reflecting the following intention: the embodiment of the present invention claimed for protection requires more features than the features clearly stated in each claim. More precisely, as reflected in the claims, the inventive aspect lies in less than all the features of the single embodiment disclosed above. Therefore, the claims following the specific embodiment are hereby explicitly incorporated into the specific embodiment, wherein each claim itself is a separate embodiment of the embodiment of the present invention.

[0047] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the embodiments of the present invention, rather than to limit them. Although the embodiments of the present invention have been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions recorded in the aforementioned embodiments, or make equivalent replacements for some of the technical features therein. However, these modifications or replacements do not deviate the essence of the corresponding technical solutions from the spirit and scope of the technical solutions of the embodiments of the present invention.

Claims

1. A method for preparing an electron-rich metal organic framework SO2 adsorbent, characterized in that: The method comprises the following steps: ZrCl4 and H3BTB-NH2 or H3TPY are added to DMF to obtain a mixed solution, ultrapure water and formic acid are added to the mixed solution, and the mixed solution is subjected to ultrasonic treatment. After the ultrasonic treatment, the mixed solution is placed in a reactor for heating. After reacting for 24 hours, the obtained suspension is centrifuged and washed several times to finally obtain a uniformly dispersed strong acid and strong alkali resistant Zr-BTB-NH2 or Zr-TPY nanosheet suspension.

2. The method for preparing an electron-rich metal organic framework SO2 adsorbent as claimed in claim 1, characterized in that: The structure of H3BTB-NH2 is as follows: ; The structure of H3TPY is as follows: 。 3. The method for preparing an electron-rich metal organic framework SO2 adsorbent as claimed in claim 1, characterized in that: The molar ratio of ZrCl4 to H3BTB-NH2 is 1.9:1-2.0:1, and the molar ratio of ZrCl4 to H3TPY is 1.9:1-2.0:

1.

4. The method for preparing an electron-rich metal organic framework SO2 adsorbent as claimed in claim 1, characterized in that: The amount of DMF solvent added is 30.0-30.2 ml.

5. The method for preparing an electron-rich metal organic framework SO2 adsorbent as claimed in claim 1, characterized in that: The amount of ultrapure water added is 4.0-4.2 ml; the amount of formic acid added is 4.0-4.2 ml.

6. The method for preparing an electron-rich metal organic framework SO2 adsorbent as claimed in claim 1, characterized in that: The power of the ultrasound is 200-300 W, and the cumulative ultrasound time is 15-20 min.

7. The method for preparing an electron-rich metal organic framework SO2 adsorbent as claimed in claim 1, characterized in that: The heating temperature is 120°C.

8. The method for preparing an electron-rich metal organic framework SO2 adsorbent as claimed in claim 1, characterized in that: The centrifugal speed is 8000-10000 r / min, the centrifugal time is 5-7 min, and the centrifugal washing operation is performed at least 5 times.

9. The Zr-BTB-NH2 or Zr-TPY nanosheets prepared by the preparation method according to claim 1 are used for SO2 gas adsorption, characterized in that: The Zr-BTB-NH2 or Zr-TPY nanosheet suspension was dried and used as a SO2 adsorbent.

10. The Zr-BTB-NH2 or Zr-TPY nanosheets prepared by the preparation method of claim 1 have excellent resistance to strong acids and bases, and are easy to desorb SO2 at room temperature.

Citation Information

Patent Citations

  • Layer functionalized two-dimensional metal organic framework coordination polymer and preparation method thereof

    CN117417549A

  • Defected NUS-8 nanosheet and preparation method thereof

    CN118290754A

  • Ultraporous organic-inorganic nanoporous composites formed by covalent bonding between inorganic-organic hybrids and mesocellular mesoporous materials

    KR1020090110041A

  • Metal-organic framework materials with ultrahigh surface areas

    WO2013192146A1